Chronic Dislocation of the 5th Metatarsophalangeal Joint with Physeal Injury of Metatarsal: A Case Report (Global Journal of Medical Research, 2019)
Metatarsophalangeal joint dislocations are uncommon injuries. This article describes the surgical management of such injury with six months follow up report. A 13 years old boy presented with the complaints of deformity and shortening of the 5 th toe of the right foot with callosity on plantar aspect since last five years. He sustained this injury by hitting a stone. He was diagnosed to have a compound dislocation of a metatarsophalangeal joint with severely angulated Salter and Harris type II epiphyseal injury of 5 th toe of the left foot. Joint dislocation caused deformed shortened 5 th toe, and epiphyseal malunion resulted in the plantar bony projection, callosity, ulceration, difficulty in walking and wearing the footwear. This case was managed surgically that culminated in an optimum functional and structural outcome. Malunited epiphysis was excised, the metatarsal bone was aligned and fixed with proximal phalanx by Kirschner wire to establish a pseudarthrosis. This method can be useful in such cases; however, needs to be evaluated with future studies.
Keywords: metatarsophalangeal joint; chronic dislocation; epiphyseal injury; pseudarthrosis